PIIL PESENGGIRI: FALSAFAH HIDUP MASYARAKAT LAMPUNG SEBAGAI BASIS KETAHANAN BUDAYA DI ERA GLOBALISASI - Utari, Marza Utari; Agustina , Dhita Aulia; Widodo, Mulyanto; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Piil Pesenggiri is a philosophy of life that contains the values of local wisdom of the Lampung people, including moral, social, and cultural principles that regulate individual, family, and community relationships. In facing the currents of globalization that bring rapid change and the challenges of cultural homogenization, Piil Pesenggiri plays a role as a basis for cultural resilience by maintaining the identity, norms, and traditions typical of Lampung alive and passed down. This study explores the concept, function, and relevance of Piil Pesenggiri in maintaining social and cultural integrity amidst the dynamics of changing times. Qualitative methods with an ethnographic approach are used to examine the practice and meaning of Piil Pesenggiri among the Lampung people. The results of the study indicate that this philosophy strengthens social solidarity and becomes a mechanism for adaptation and protection of cultural values, thereby strengthening cultural resilience in facing the challenges of globalization.